(untitled) (CIPEEX, 2025)
Global population aging poses significant challenges to public health, especially with regard to the increased risk of falls among older adults, which can be exacerbated by conditions such as hypertension. These factors are associated with health problems that can lead to serious accidents, loss of autonomy, and reduced quality of life for older adults. The objective of this study was to compare the risk of falls, lower limb muscle strength, and postural balance in older adults with and without hypertension. A cross-sectional analytical observational study was conducted with 106 older adults enrolled at UniAPI, of whom 10 met the inclusion criteria. Sociodemographic information was collected, and assessments of fall risk, cognitive level, and muscle strength were performed. The results showed that hypertensive elderly individuals performed significantly worse on the Sit-to-Stand Test (STT) compared to healthy individuals, reflecting reduced functional capacity. However, no significant differences in postural balance were found between elderly individuals with and without hypertension, as indicated by the values of displacement and speed of the center of gravity. These findings indicate that when hypertension is controlled, there is no impact on postural balance control. The absence of significant differences reinforces the need for intervention strategies to improve mobility and muscle strength in patients with cardiovascular conditions, aiming to prevent falls and improve the quality of life of older adults.